Carvedilol protects the kidneys of tumor-bearing mice without impairing the biodistribution or the genotoxicity of cisplatin. (5th February 2016) - Carvalho Rodrigues, Maria A.; Santos, Neife A.G. dos; da Silva Faria, Marcia C.; Rodrigues, Jairo Lisboa; Kinoshita, Angela; Baffa, Oswaldo; Antunes, Lusania M. Greggi; Barbosa, Fernando; Gobe, Glenda C.; Santos, Antonio Cardozo dos
Abstract: Cisplatin (Cisp) is an effective antitumor drug; however, it causes severe nephrotoxicity. Minimization of renal toxicity is essential, but the interference of nephroprotective agents, particularly antioxidants, with the antitumor activity of cisplatin is a general concern. We have recently demonstrated that the anti-hypertensive and antioxidant drug carvedilol (CV) protects against the renal damage and increases the survival of tumor–bearing mice without impairing the tumor reduction by cisplatin. So far, reports on the antioxidant mechanism of CV are controversial and there are no data on the impact of CV on the antitumor mechanisms of cisplatin. Therefore, this study addresses the effect of CV on mechanisms underlying the tumor control by cisplatin. CV did not interfere with the biodistribution or the genotoxicity of cisplatin. We also addressed the antioxidant mechanisms of CV and demonstrated that it does not neutralize free radicals, but is an efficient chelator of ferrous ions that are relevant catalyzers in cisplatin nephrotoxicity. The present data suggest that oxidative damage and genotoxicity play different roles in the toxicity of cisplatin on kidneys and tumors and therefore, some antioxidants might be safe as chemoprotectors. Altogether, our studies provide consistent evidence of the beneficial effect of CV on animals treated with cisplatin and might encourage clinical trials. Highlights: Carvedilol protects against the nephrotoxicity of cisplatin in tumor-bearing mice. Carvedilol does not affect the genotoxicity or biodistribution of cisplatin. Carvedilol is not an efficient scavenger of free radicals. Carvedilol efficiently chelates ferrous ion. The antioxidant mechanism might involve inhibition of the Fenton reaction.